1999
DOI: 10.1046/j.1365-2745.1999.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual growth rings, rainfall‐dependent growth and long‐term growth patterns of tropical trees from the Caparo Forest Reserve in Venezuela

Abstract: Summary0 Tree!ring analyses and dendrometer measurements were carried out on 26 tree species in a semi!deciduous forest of the Reserva Forestal de Caparo\ Venezuela\ where the mean annual rainfall is about 0699 mm and there is a dry season from December to March[ The main purposes of the investigation were to show the seasonality of cambial growth\ and the connection between precipitation patterns and tree!ring curves[ Long!term rates of wood increment were also estimated[ 1 Cambial markings in consecutive yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
257
3
39

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(341 citation statements)
references
References 30 publications
25
257
3
39
Order By: Relevance
“…In a semi-deciduous forest in Ghana, shade intolerant pioneer species associated with high-rainfall forest with less fertile soil, had significantly lower growth rates than pioneers that are more abundant in low-rainfall forest with more fertile soils (Baker et al, 2003). While working on tree ring chronologies of seven tree species in a semi-deciduous forest in Venezuela, Worbes (1999) reported a positive correlation between annual rainfall and growth rates. At three sites in a seasonal forest in Panama, Devall et al (1995) found that annual rainfall correlated with variations in tree ring width for three species.…”
Section: Introductionmentioning
confidence: 96%
“…In a semi-deciduous forest in Ghana, shade intolerant pioneer species associated with high-rainfall forest with less fertile soil, had significantly lower growth rates than pioneers that are more abundant in low-rainfall forest with more fertile soils (Baker et al, 2003). While working on tree ring chronologies of seven tree species in a semi-deciduous forest in Venezuela, Worbes (1999) reported a positive correlation between annual rainfall and growth rates. At three sites in a seasonal forest in Panama, Devall et al (1995) found that annual rainfall correlated with variations in tree ring width for three species.…”
Section: Introductionmentioning
confidence: 96%
“…Contribuir com o estabelecimento do manejo racional da florestal exige dados confiáveis de crescimento. Embora seja antiga a controvérsia sobre a formação de anéis anuais em madeiras tropicais, devido a ausência de estações climáticas marcadas (Lieberman e Lieberman 1985), as análises de anéis de crescimento em florestas tropicais vêm ganhando credibilidade com estudos que comprovam a existência para algumas espécies de interesse comercial, como Cedrela odorata e Swietenia macrophylla, ambas as espécies da família Meliaceae (Dünisch et al 2003;Worbes 1999). Portanto, isso viabiliza a aplicação de métodos dendrocronológicos para obter dados de crescimento para modelagem.…”
Section: Introductionunclassified
“…Em espécies tropicais, o crescimento das árvores depende da disponibilidade de água, ocorrendo, em geral, a redução do crescimento durante a estação seca (WORBES, 1999;LISI et al, 2008;CALLADO et al, 2013) ou durante o período chuvoso, já que o excesso de água no solo pode levar a raiz a um estado de hipóxia, reduzindo sua atividade e, consequentemente, causando um déficit de água no tronco (SCHÖNGART et al, 2002). Em remanescentes da Floresta Estacional Semidecidual do Estado de São Paulo foi constatado que o CCT de 24 espécies arbóreas foi menor durante a estação seca e reativado após as primeiras chuvas significativas no início da estação chuvosa (LISI et al, 2008).…”
Section: Introductionunclassified